Analysis of plastics packaging domestic market - Czerniawski, B. (Polimery, 2022)
The article contains the results of analysis of plastics packaging domestic market and the description of the analysis method used (Table 1). The data presented are put in relation to particular analyzed segments of the market, i.e. flexible materials and packaging (including PE, PP and multilayer ones); materials thermoformed from rigid films; those formed by blow extrusion or blow injection, as well as injection molded ones. The tendencies of growing consumption of particular packaging types, observed during last 5 years, were characterized. The forecast directions of further development were marked and present and forecast importance of flexible packaging has been stressed.